2020
DOI: 10.1186/s12882-020-01785-x
|View full text |Cite
|
Sign up to set email alerts
|

The fertility willingness and acceptability of preimplantation genetic testing in Chinese patients with autosomal dominant polycystic kidney disease

Abstract: Background: With the development and progression of genetic technology, preimplantation genetic testing (PGT) has made it possible to block the inheritance of autosomal dominant polycystic kidney disease (ADPKD) as early as possible. However, we need to know the patients' fertility intentions and their acceptance of PGT. Methods: A questionnaire survey was conducted to collect data on the basic demographic data, quality of life, social support, fertility willingness, and level of understanding of genetic testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
2
Order By: Relevance
“…In China, a study assessed the acceptability of PGT among patients with autosomal dominant polycystic kidney disease. In that study, 60.4% of the respondents were aware that PGT technology can diagnose and modify the outcome of disease inheritance, and 79.6% of patients will choose PGT if they would plan for children in the future [ 12 ]. Recently a study has been conducted to know the awareness about genetic testing on 333 participants at King Saud University, Riyadh, Saudi Arabia, has also found a majority of their respondents (85.6%) agreed with having premarital genetic testing like our study in which the majority has displayed a positive attitude towards PGT.…”
Section: Discussionmentioning
confidence: 99%
“…In China, a study assessed the acceptability of PGT among patients with autosomal dominant polycystic kidney disease. In that study, 60.4% of the respondents were aware that PGT technology can diagnose and modify the outcome of disease inheritance, and 79.6% of patients will choose PGT if they would plan for children in the future [ 12 ]. Recently a study has been conducted to know the awareness about genetic testing on 333 participants at King Saud University, Riyadh, Saudi Arabia, has also found a majority of their respondents (85.6%) agreed with having premarital genetic testing like our study in which the majority has displayed a positive attitude towards PGT.…”
Section: Discussionmentioning
confidence: 99%
“…Among individuals unsure about pursuing PGT, half cited technical safety as the most common concern. 58 Patient preference studies indicate that 80% of couples at risk for transmitting a monogenic disorder prefer PGT-M over alternatives such as adoption, donor gamete use, or prenatal diagnosis. 59 For patients in the United Kingdom with ADPKD, most wanted to be offered the option of PGT-M. 60 The broad application of these data to other populations is unclear because similar studies are currently limited in the United States and other parts of the world.…”
Section: Pgt-m For Pkdmentioning
confidence: 99%
“…97 Over 50% of queried patients with ADPKD reported that the safety of PGT was not clear after informed consent. 58 In clinics offering PGT in the United States, only 56% offered pretest genetic counseling, and only 84% of these instances involved certified genetic counselors. 98 Thus, a lack of standardized informed consent and pretest genetic counseling practices for PGT can lead to variability and added ethical challenges.…”
Section: Federal Regulations and Professional Self-regulationmentioning
confidence: 99%
“…Al fine di facilitare le decisioni riguardanti la pianificazione familiare e di migliorare l'accesso a tali servizi, è opportuno fornire alle pazienti informazioni dettagliate sulle opzioni relative alle tecniche di procreazione medicalmente assistita (PMA) (6,13,15). Negli ultimi decenni, la fecondazione in vitro di terza generazione (IVF) e il test genetico preimpianto (PGT) sono stati utilizzati con successo per garantire la nascita di bambini non affetti da ADPKD (14,16).…”
Section: Tecniche DI Procreazione Medicalmente Assistita (Pma)unclassified
“…Dalla letteratura emerge che le donne con policistosi renale tendono ad avere meno gravidanze. Infatti, solo il 45% delle pazienti in età fertile ha l'intenzione di avere figli, un numero ancora inferiore se le donne presentano già un'insufficienza renale cronica (chronic kidney disease, CKD) (6,7). Questa ridotta propensione alla maternità è correlata principalmente alla preoccupazione riguardante l'ereditarietà della malattia.…”
Section: Adpkd E Il Desiderio DI Maternitàunclassified